Two species of Dolichomitus Smith, 1877 (Hymenoptera, Ichneumonidae, Pimplinae) parasitizing borers of Juglans mandshurica Maxim. and a key to species known from China - Sheng, Mao-Ling; Lü, Jun; Liao, Cheng-Jia; Li, Tao; Sun, Shu-Ping (European Journal of Taxonomy, 2022)
Two species of Dolichomitus Smith, 1877 emerged from the trunks of Juglans mandshurica Maxim. in Kuandian and Benxi Manzu Autonomous Counties, Liaoning, in the Palaearctic part of China. One new species, D. juglanse Sheng #38; Li sp. nov., reared from Menesia flavotecta Heyden, 1886 and Mesosa myops (Dalman, 1817) (Cerambycidae), is described and illustrated. A key to the species of Dolichomitus known from China is provided.